Determinants of Capital Structure in Indonesia's Food and Beverage Sector: Faktor Penentu Struktur Modal di Sektor Makanan dan Minuman Indonesia - Nurmalianto, Achmad Hilmi Ardiansyah; abidin, Fityan izza noor (Indonesian Journal of Law and Economics Review, 2024)
This study examines the impact of company growth, profitability, and asset structure on the capital structure of food and beverage companies listed on the Indonesia Stock Exchange from 2015 to 2019. Using a purposive sampling method, 8 companies were analyzed through SPSS. The results indicate that company growth, profitability, and asset structure significantly influence capital structure. These findings offer valuable insights for financial managers in optimizing capital structure and contribute to the academic understanding of capital structure determinants in emerging markets. Highlight: Significant impact on capital structure by growth, profitability, asset structure. Analyzed food and beverage companies on Indonesia Stock Exchange, 2015-2019. Provides financial managers insights for optimizing capital structure decisions. Keyword: company growth, profitability, asset structure, capital structure, food and beverage